NMR-Based Metabolic Profiling and Anticancer Activity of Nephelium ramboutan-ake and Nephelium lappaceum Flesh - Febrina, Lizma; Rusli, Rolan; Samsul, Erwin; Rijai, Laode; Ahmad, Islamudin; Rusman, Arman; Hikmawan, Baso Didik; Rija'i, Hifdzur Rashif; Almeida, Maria (Indonesian Journal of Chemistry, 2026)
In this research, 1H-NMR-based metabolomics assessed the metabolite profiles of two Nephelium species flesh, specifically Nephelium ramboutan-ake and Nephelium lappaceum. Our research findings indicate that the metabolite profile of N. ramboutan-ake is qualitatively identical, although numerically distinct from that of N. lappaceum. The PLSDA data indicate that N. ramboutan-ake possesses elevated concentrations of acetic acid, malic acid, GABA, and succinic acid compared to N. lappaceum. In N. lappaceum, alanine and glucose serve as the distinguishing metabolites. Additionally, the anticancer efficacy of two Nephelium samples was assessed. As a result, the anticancer properties of N. ramboutan-ake were superior to those of N. lappaceum. PLS analysis indicated that GABA exhibited the most positive connection with the anticancer activity of Nephelium samples. These results indicate that the higher GABA concentrations of N. ramboutan-ake have a beneficial effect on its anticancer activity.